Accounting for the Holocaust : enabling the Final Solution - Funnell, Warwick; Bigoni, Michele; Twyford, Erin (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Accounting for the Holocaust reveals how accounting practices allowed the attempted annihilation of Jews by the German Nazis and the Italian Fascists to be carried out with machine-like efficiency and devoid of any moral considerations. This largely hidden aspect of the Holocaust will allow a wide range of readers, both academic and across many sectors of the general population, to understand how the systematic murder of more than six million Jews was expedited by accounting practices and the information that these produced by allowing the humanity of those killed to be denied when they became mere numbers in a process. Readers will gain a new understanding of how the enactment of the scale of the Holocaust was made possible by the way in which accounting practices as 'technologies of death' were used to reduce Jews to a life without value. The numerical calculations, techniques and reports that constitute accounting practices allowed the systematic murder of Jews to be drained of any considerations that would imply that the numbers and costings were related to prescient human beings. These technologies of death also allowed those who managed and organised the murder of Jews to absolve themselves of the actual killings"--
Keywords: Accounting -- Germany -- History -- 20th century; Accounting -- Moral and ethical aspects -- Germany; Holocaust, Jewish (1939-1945) -- Economic aspects; BUSINESS & ECONOMICS / Accounting / General; HISTORY / Holocaust; BUSINESS & ECONOMICS / Economic History